In vitro regeneration of plantlets from leaf segments of Pupalia lappacea (L.) Juss. for mass propagation - Vijayan, V.; Vijayakumar, K. K. (Current Botany, 2023)
The in vitro study was carried out to standardize the protocol for induction of callus, proliferation of shoots, initiation of roots, and plant regeneration in Pupalia lappacea (L.) Juss. using the artificial nutrient culture medium. Maximum callus induction (76%) from the young leaf explants was achieved by using MS medium supplemented with 0.5 mg L-1 of 2, 4-D and 2.5 mg L-1 of NAA. The maximum shoot induction (78%) was observed on MS medium containing 2.0 mg/L of BAP and 0.8 mg/L of GA3. The highest root initiation (70%) was obtained on MS medium with IBA (1.2 mg L-1) and IAA (0.5 mg L-1). The acclimation process was successfully completed in the garden soil with a better survival rate (72%).